THE ROLE OF PEASANT FARMS IN THE DEVELOPMENT OF AGRICULTURE - Shuhrat Bafoyevich Adizov. Shakhzod Salimov Odiljon o’g’li, Rajabov Azizbek G’ulom o’gli. Bukhara institute of natural resourses management (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
The little family dehkan farms of household goods, personal based on the work of the family members, inheritance left to possess a plot of land given to the head of the family lifetime and will produce agricultural product of the sale.